Public Debt and GDP Growth in WAEMU Countries - Hou, Junru (Université d'Ottawa | University of Ottawa, 2020)
This paper tests the relationship between public debt and GDP per capita growth in WAEMU countries between 1980 and 2015 using panel data regression model. The influence on economic growth can be reflected by the changes in not only public debt but also other economic factors, such as the initial GDP per capita growth, openness, etc... There are three ways to solve panel data regression model: pooled OLS estimation, fixed effects estimation, and random effects estimation. Based on the assumptions and the results, dummy variables estimation, one of the methods of fixed effect estimation, is the preferred model. According to the results, a 1% increase in public debt will lead to a 0.014% slowdown in GDP per capita growth. Public debt can affect growth negatively with statistical insignificance; thus, public debt does not seem to negatively affect growth. Regarding to debt threshold, although debt thresholds vary across countries, there exists a common range of the debt thresholds in WAEMU countries: around 40%-60%, based on the two-way plots.